Pemikiran Maqasid Al-syari‘at Dalam Ekonomi Islam Arus Perdana: Satu Penilaian - Ahmad, Norashikin (2023)
The maqasid al-syari‘at thought refers to a school of thought in maqasid al-syari‘at that exists in understanding the knowledge of maqasid al-syari‘at. It is a knowledge discipline in the field of usul al-fiqh which currently draws attention. The main factor leading to its use is because this knowledge discipline covers the entire aspects of human life. In line with the current advancement, maqasid al-syari‘at also experiences its own phases of progress to the point it becomes an exceedingly crucial knowledge discipline. This is due to the coming of diverse schools of thought which exist in understanding maqasid al-syari‘at. It has been applied in a myriad of fields including Islamic economics. However, there have been claims stating that Islamic economics scholars are still acceptive of the tasawur, philosophical foundations, and definitions of conventional economics. The question is, does maqasid al-syari‘at underlie the constructive aspects in the mainstream Islamic economics? How is maqasid al-syari‘at stated or applied in the mainstream Islamic economics? Based on these problems, this study will be conducted based on three main objectives. First, to identify the concept of the maqasid al-syari‘at thought in the mainstream Islamic economics; second, to analyse the maqasid al-syari‘at thought in the mainstream Islamic economics; third, to formulate the pattern of the maqasid al-syari‘at thought in the mainstream Islamic economics. To achieve the objectives, this study utilized a basic qualitative design and used secondary data comprising a variety of prior books, research, and work and so forth